Boron Deficiency in Palms - Timothy K. Broschat (EDIS)
Chronic boron deficiency is believed to be caused by soil drying and high soil pH, while temporary deficiency is caused by heavy leaching. It results in a wide array of symptoms, not only among species of palms, but also within a single species. This revised 5-page fact sheet contains many illustrations to aid in diagnosis and management recommendations. Written by Timothy K. Broschat and published by the UF Department of Environmental Horticulture, June 2011.